African financial markets and global uncertainties: nonlinearities, asymmetries, and information flow - Dadzie, Emmanuel (University of the Witwatersrand, Johannesburg, 2024)
The global economy has witnessed rapid integration of financial markets, resulting in increased interdependence. This thesis investigates how global uncertainties or shocks impact African financial markets, focusing on both stock markets and currencies. The study examines how African markets have become more exposed to shocks, uncertainties, and spillover effects originating from other regions, particularly during crises and pandemics. Given the increasing significance of global policy shocks in investment decisions, portfolio design, and risk management, this research seeks to fill the gap in understanding the robustness of African markets in the face of such challenges. It employs advanced econometric models to capture nonlinearities, asymmetries, and information content flow within a time-frequency domain, addressing the underexplored areas of the literature. The thesis covers African stocks or equities markets and currencies. The selection of markets reflects the diverse economic landscapes and conditions across the continent. Prominent stock exchanges such as the Nigerian Stock Exchange, Botswana Stock Exchange, Egyptian Exchange, Tunis Stock Exchange, Namibian Stock Exchange, Moroccan All Shares Index, Ghana Stock Exchange, Lusaka Stock Exchange, and the Johannesburg Stock Exchange Africa All Share Index in South Africa have been captured. In addition to the stocks or equities markets, the choice of currencies also reflects the economic diversity and regional dynamics across the continent. These include the Egyptian Pound, the South African Rand, the Nigerian Naira, the Tunisian Dinar, the Ghanaian Cedi, the Moroccan Dirham, the Botswana Pula, the Mauritian Rupee, the iii Kenyan Shilling, the Namibian Dollar, and the West African CFA Franc. The global uncertainties or global shocks used in this thesis are the US Economic Policy Uncertainty Index, Oil Volatility Index, and Volatility Index. These indices are crucial indicators of economic instability and market sentiment and provide insights into the level of uncertainty surrounding economic policies, oil prices, and overall market volatility. The analysis covers 1 January 2010 to 31 December 2022 giving 3,379 daily observations for each variable. The thesis is organized into six chapters, with three self-contained empirical chapters. Each empirical chapter focuses on one specific objective or research question. The first empirical chapter examined the information flow between African stocks and global uncertainties using advanced analytical techniques. Employing the Complete Ensemble Empirical Mode Decomposition with Adaptive Noise method for data decomposition and the Rényi effective transfer entropy technique for information exchange estimation, the relationships between economic policy uncertainty, oil volatility index, CBOE volatility index, and African stock markets are investigated. The findings reveal both significant and insignificant positive information flows between US Economic Policy Uncertainty and African stocks across different investment horizons. Similar trends were observed with the oil volatility index and the CBOE volatility index, indicating a consistent pattern of information exchange. Importantly, no significant negative transfers were observed, suggesting a limited risk of contagion and high market resilience. Moreover, all three global uncertainty indices were identified as net positive information senders to African stocks across various investment horizons. iv The second objective investigates the effect of global uncertainties on the currencies of both oil-exporting and oil-importing African currencies. The Chapter reveals asymmetrical relationships with generally positive associations, suggesting currency depreciation during changes in global shocks. Employing the Variational Mode Decomposition technique, the time series data is decomposed to reveal underlying patterns and dynamics. The results of the quantile regression model reveal asymmetries in the effects of these shocks on currency rates, with generally positive associations suggesting currency depreciation amidst fluctuations in global uncertainties. The study highlights mixed effects across different quantiles and market conditions. Short-term, medium-term, and long-term analyses reveal the varying effects of global uncertainties on African currency rates, which provides revelations into the dynamics shaping currency movements in Africa. The third objective also applies the Variational Mode Decomposition technique and the nonlinear causal technique by Diks and Panchenko (2006) to investigate the effects of global uncertainties on the currencies of oil-exporting and oil-importing African countries, across various time frames. The findings of the robust nonparametric causal tests reveal interesting patterns in the relationships between global shocks and African currencies. Notably, the US Economic Policy Uncertainty demonstrates a significant causal impact on the Ghanaian Cedi, while other oil-exporting and oil-importing currencies exhibit varied responses to global economic shocks. The Oil Volatility Index exerts short to medium- term influences on specific currency rates, with differential effects observed between v exporting and importing countries. Similarly, the Volatility Index affects the returns of certain currencies, highlighting the connectedness between global uncertainties and African currency markets. The evidence of asymmetric effects of global uncertainties on African financial markets and the diverse exposure of oil-exporting and oil-importing economies underscore the importance of considering country-specific contexts and economic structures in analyzing the impact of global shocks on the dynamics of African markets. Efforts by monetary and fiscal policymaking fronts to enhance market integration and improve information dissemination mechanisms are crucial to help African financial markets better respond to global uncertainties while minimizing adverse effects. The thesis offers valuable insights for policymakers, investors, and corporate bodies navigating African markets
A research report submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: FINANCIAL MARKETS; GLOBAL UNCERTAINTIES; NONLINEAR CAUSALITY; QUANTILE REGRESSION; TIME SERIES DECOMPOSITION; TRANSFER ENTROPY; SDG-8: Decent work and economic growth; SDG-8: Decent work and economic growth